New species and notes on Meconematini (Orthoptera: Tettigoniidae: Meconematinae) from southern Taiwan - Chen, Po-Wei; Chan, Ming-Shu; Tan, Ming Kai (Zootaxa, 2025)
Recent orthopteran sampling was conducted by the authors in Pingtung County in the southern part of Taiwan. A new species of Taiyalia Yamasaki, 1992 is described: Taiyalia meridionalis sp. nov. We also report new locality records for: Leptoteratura taiwana Yamasaki, 1987, Neocyrtopsis (Neocyrtopsis) longicauda Chen & Wu, 2025, and Xizicus (Eoxizicus) taiwanensis Chang, Du & Shi, 2013; as well as Teratura (Teratura) cincta (Bey-Bienko, 1962) and Xiphidiopsis (Euxiphidiopsis) autumnalis (Gorochov, 1998) in Nantou County at the central part of Taiwan.